Z-scheme induced g-C3N4 /WS2 heterojunction photocatalyst with improved electron mobility for enhanced solar photocatalysis. (1st November 2021) - Nawaz, Ahmad; Goudarzi, Shaghayegh; Saravanan, Pichiah; Zarrin, Hadis
Graphical abstract: Highlights: g-C3 N4 /WS2 heterojunction was synthesized through one-pot hydrothermal method. The nanocomposite boosted solar light utilization and stabilized electron movement. Charge mobility via Z–scheme mechanism with strong hindrance of recombination. Superior photocatalysis irrespective of the photosensitizing nature of pollutants. Abstract: This study reports the hybridization of g-C3 N4 /WS2 prepared through one-pot hydrothermal synthesis in the absence of a reducing agent. Heterojunction samples of varied WS2 compositions and fixed g-C3 N4 concentrations (CNW-0.5, CNW-1.0 and CNW-1.5) were synthesized. All samples were physiochemically and electrochemically examined to understand their materials' chemistry and performance. The particle size of the composite varied from 2.55 µm to 2.58 µm with a high crystalline structure. The Nyquist Plot demonstrated an improved charge mobility, and the transient photo current showed a prolonged lifetime of the charge carriers for the CNW-1.0 sample. The Mott Schottky plot proved the p-n junction formation of the composite with a potential energy barrier at the junction. The time-resolved transient PL decay curves demonstrated an average lifetime ( τ avg ) of 8.51 μ s for CNW-1.0, which was 2.6 times higher than that of WS2 alone. The highest solar photocatalytic degradation of 95.5% for Methylene Blue and 84.5% for Tetracycline were achieved with CNW-1.0 in 2 h, where ( ̇ O2 – ) and (OH ̇ ) radicals were dominant in the reaction. The obtained band positions suggested the Z-Scheme mechanism for the charge mobility across the heterojunction. The developed p-n heterojunction photocatalyst proved its ability in utilizing the solar energy for a robust photocatalysis reaction.